Portable rapid detection of maize chlorotic mottle virus using RT-RAA/CRISPR-Cas12a based lateral flow assay - Lei, Rong; Kuang, Ruirui; Peng, Xuanzi; Jiao, Zhiyuan; Zhao, Zhenxing; Cong, Haolong; Fan, Zaifeng; Zhang, Yongjiang (Frontiers in Plant Science, 2023)
Introduction Maize lethal necrosis seriously threatens maize production worldwide, which was caused by coinfection by maize chlorotic mottle virus (MCMV) and a potyvirid. To effectively control maize lethal necrosis, it is vital to develop a rapid, sensitive, and specific detection method for the early diagnosis of MCMV in host plant tissues. Methods We established a rapid detection procedure by combining the one-step reverse-transcription recombinase-aided amplification (one-step RT-RAA) and CRISPR/Cas12a-based lateral flow assay in one tube (one-tube one-step RT-RAA/CRISPR-Cas12a), which can be implemented on a portable metal incubator at 37~42°C. Furthermore, the crude extract of total RNA from plant materials using alkaline-PEG buffer can be directly used as the template for one-step RT-RAA. Results The developed one-tube one-step RT-RAA/CRISPR-Cas12a lateral flow assay can detect as low as 2.5 copies of the coat protein (CP) gene of MCMV and 0.96 pg of the total RNA extracted from MCMV infected maize leaves. Furthermore, the MCMV infected maize leaves at 5 dpi having no obvious symptoms was detected as weak positive. Discussion The crude extraction method of total RNA from plant materials required no complicated device, and all the procedures could be implemented at room temperature and on a portable metal incubator, costing a total time of about 1h. The one-step RT-RAA reagents and CRISPR/Cas12a reagents can be lyophilized for easy storage and transportation of reagents, which makes this method more feasible for the filed detection. This method presents rapidness, robustness and on-site features in detecting viral RNA, and is a promising tool for the field application in minimally equipped laboratories.